Chapter 10 Understanding How the Internet and Social Media Accelerate Racial Stereotyping and Social Division: The Socially Mediated Stereotyping Model - Dixon, Travis L. (Taylor & Francis, 2016)
This volume will feature research examining the consequences, implications, and opportunities associated with issues of diversity in the electronic media. The topics of gender and race in electronic media have been hot topics of study and remain so today. The book will consider race and gender issues in both historical and contemporary (including newly emerging) electronic media, and will focus on: 1) media content, 2) media audiences, and 3) media production. Chapters may reflect the intersection of race and gender, or overlap with either race or gender and other types of difference such as class, religion, and physical ability.